A Study on the Treatment of Hyperkeratotic and Scaling Disorders Using Salicylic Acid Film Forming Gel with It’s Development and Characterization - Kausdikar , Rajashri N.; Kondawar , Manish S.; Jadhav , Priyanka H.; Jaiswal , Nayna M.; Mali , Ramling D. (Advanced Concepts in Pharmaceutical Research Vol. 1, 2023)
In order to overcome the drawbacks of traditional topical formulation, the goal of this study is to design and characterize a salicylic acid film-forming gel of hydrophilic polymers for the treatment of hyperkeratotic and scaling disorders that has wipe-off resistance, longer retention at the treatment site, and is simple to spread and apply to the skin. Hyperkeratosis refers to the increased thickness of the stratum corneum, the outer layer of the skin. It is most frequently due to chronic physical or chemical damage such as friction or the use of aggressive soaps but can also derive from chronic inflammation or a side-effect of different drugs, including chemotherapy. Salicylic acid can be used topically to treat hyperkeratotic disorders, which are skin conditions characterized by red, dry, cracked, and scaling skin. The film-forming gel is prepared with HPMC E15, carbopol 934, propylene glycol, water, ethanol, and the drug. It is then optimised using 22 factorial designs and is characterised by its physical characteristics, pH level, spreadability, drug content, rheological study, in vitro drug release, drying time, mechanical properties of the film, and other factors. Salicylic acid film-forming gel stability, skin irritancy, ex vivo permeation, and skin retention were also investigated. For certain tests, every formulation produces the expected results. The optimisation analysis found that viscosity increases and drug release decreases when HPMC E15 and carbopol 934 concentrations rise. The improved formulation had a viscosity of 47.6 ± 1.23 cp and a 90.23 ± 2.01% drug release. It is concluded that salicylic acid film-forming gel for the treatment of hyperkeratotic and scaling diseases is efficiently produced with hydrophilic polymers i.e., HPMC E15 and Carbopol 934 and which has wipe off resistance, longer retention at the site of treatment, easy to spread on application and it forms a thin, transparent, protective, emollient and water soluble film on skin within few minutes to overcome the disadvantages of convention topical formulation like ointment, cream, gel i.e. need to rubbing, poor adherence to the skin, easily wiped off due to clothes, sweat, movements, poor permeability, compromised patient compliance.